2020
DOI: 10.1111/cpr.12969
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanisms of basic fibroblast growth factor on the proliferation and regenerative profiles of cryopreserved dental pulp stem cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…In comparison, dental pulp stem cells (DPSCs), originated from neural crest and enclosed in a dental pulp chamber, seem to be an excellent source of stem cells. Because DPSCs can be extracted from discarded teeth, which is non‐invasive and raises no ethic concerns 7,8 . A recent animal study showed that exosomes secreted from DPSCs had stronger immuno‐modulating effects than those from the BMSCs 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, dental pulp stem cells (DPSCs), originated from neural crest and enclosed in a dental pulp chamber, seem to be an excellent source of stem cells. Because DPSCs can be extracted from discarded teeth, which is non‐invasive and raises no ethic concerns 7,8 . A recent animal study showed that exosomes secreted from DPSCs had stronger immuno‐modulating effects than those from the BMSCs 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Because DPSCs can be extracted from discarded teeth, which is non‐invasive and raises no ethic concerns. 7 , 8 A recent animal study showed that exosomes secreted from DPSCs had stronger immuno‐modulating effects than those from the BMSCs. 9 An intravenous administration of DPSCs was proved to confer a similar functional recovery and superior reduction in infarct size following the middle cerebral artery occlusion in a rat model compared with the administration of BMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, ad-SVF spheroids could secrete more growth factors than ad-SVF and promote endothelial cell migration, which indicate a better recovery effect in UAB induced by PBOO. bFGF, as a member of FGFs, is demonstrated to suppress cell apoptosis and promote proliferation [35]. HGF was reported to be a potential anti-brotic factor in damaged tissues and pro-angiogenic factor, which has similar effects with VEGF-A [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The mitogenic effect of the bFGF on dental pulp cells was also supported recently by adding it in culture medium. Promising results were received in that the bFGF significantly promoted the proliferation of DPSCs through activating the ERK pathway without comprising cell stemness and pluripotency ( Luo et al, 2021 ). With no exceptions, the mitogenic potential of the bFGF on SHEDs was also found ( Sukarawan et al, 2014 ), and further study revealed that the bFGF promoted SHED colony-forming units via the FGFR/PI3K pathway ( Nowwarote et al, 2020 ).…”
Section: The Underlying Mechanisms Of Basic Fibroblast Growth Factor In Dental Pulp Repair and Regenerationmentioning
confidence: 99%
“…Taking those pieces of evidence together, the bFGF has the superiority to promote cell proliferation and control the cell cycle progression via stimulating the expression of related genes and proteins, including Ki67, cdc2, and cyclin B1. Therefore, its mitogenic effect can be put into use to amplify the cell number in order to obtain the sufficient amount of stem cells required for endodontic regenerative treatments and can also brighten the future of stem cell banking and tissue engineering ( Luo et al, 2021 ).…”
Section: The Underlying Mechanisms Of Basic Fibroblast Growth Factor In Dental Pulp Repair and Regenerationmentioning
confidence: 99%